2017
DOI: 10.1016/j.polymer.2017.02.069
|View full text |Cite
|
Sign up to set email alerts
|

Distyrylbenzene-based segmented conjugated polymers: Synthesis, thin film morphology and chemosensing of hydrophobic and hydrophilic nitroaromatics in aqueous media

Abstract: Two new segmented conjugated polymers bearing distyrylbenzene chromophoric units and their model compounds were synthesized. The tendency of the model compounds to form H-and J-type aggregates in the amorphous matrix was greatly diminished by the twisted polymeric architecture. Fluorescence anisotropy measurements indicated good exciton mobilities in condensed phase. Fluorescence quenching by nitroaromatic aqueous solutions was fast, complete, selective and reversible pointing to a rapid diffusion of analytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The reaction of the dibromides with triethylphosphite afforded the bisphosphonates 1a and 1b [28]. Aldehyde 2 and dialdehyde 3 were prepared according to the literature [13]. The details of the synthesis and characterization of the synthetic precursors, monomer, model compounds M14 and M26 and the polymers P14 and P26 are presented in Supplementary Materials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction of the dibromides with triethylphosphite afforded the bisphosphonates 1a and 1b [28]. Aldehyde 2 and dialdehyde 3 were prepared according to the literature [13]. The details of the synthesis and characterization of the synthetic precursors, monomer, model compounds M14 and M26 and the polymers P14 and P26 are presented in Supplementary Materials.…”
Section: Methodsmentioning
confidence: 99%
“…In order to obtain amorphous morphologies that could favor diffusion of the analyte from the aqueous solution into the polymeric film, we knitted semi-rigid fluorophores with isopropylene units, which confer a highly twisted nature to the main chain. We found that thin films of these disordered assemblies of fluorophores proved to be very sensitive towards NACs in aqueous media [12,13]. Indeed, we and many others have found that different fluorescent materials [14,15,16,17,18,19,20,21,22,23,24], despite their huge disparity in chemical structure, are very responsive in aqueous media towards picric acid (PA) and show no, or a small, responses to trinitrotoluene (TNT) and related nitrotoluenes.…”
Section: Introductionmentioning
confidence: 99%
“…In another example, distyrylbenzene conjugated segments were linked by isopropylene spacers to generate a segmented conjugated polymer that responded to nitroaromatic analytes with a strong decrease in fluorescence (Figure a) . Of note, distyrylbenzene as a chromophore has been reported as a key component of luminescent amine sensors and as part of proton sensing for pH detection schemes .…”
Section: Luminescent Polymer Sensorsmentioning
confidence: 99%
“…These values are among the best in the published literature. 23,29,49,50 The response of dispersed PTPA1-TPE nanoaggregates towards other aromatic analytes have been also tested, as shown in Fig. 6.…”
Section: Explosive Detectionmentioning
confidence: 99%